2019
DOI: 10.1186/s12870-019-2213-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the TCA cycle genes in maize

Abstract: BackgroundThe tricarboxylic acid (TCA) cycle is crucial for cellular energy metabolism and carbon skeleton supply. However, the detailed functions of the maize TCA cycle genes remain unclear.ResultsIn this study, 91 TCA genes were identified in maize by a homology search, and they were distributed on 10 chromosomes and 1 contig. Phylogenetic results showed that almost all maize TCA genes could be classified into eight major clades according to their enzyme families. Sequence alignment revealed that several gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Multiple elements were identified, and the stress and hormone signaling-related sites are shown in Table 2 . The table describes information pertaining to functions, such as elements in response to hormones, including abscisic acid (ABRE, CE1, and MRE) (Narusaka et al 2003 ), salicylic acid (TCA element) (Liu et al 2020 ), ethylene (ERE) (Song et al 2019 ), gibberellin acid (GARE-motif, P-box and TATC-box) (Zhang et al 2017 ), auxin (TGA-element) (Xin et al 2016 ), MeJA (CGTCA-motif and TGACG-motif) (Yu et al 2018 ), temperature-responsive elements (HSE and LTR) (Wu et al . 2019 ), drought-inducible elements (MBS) (Xu et al 2019 ), wound-responsive element (WUN-motif), defense and stress element (TC-rich repeats) (Li et al 2019 ), salt-inducible element (GT1-motif), anaerobic induction element (ARE), and light- and nitrogen-inducible element (GATA-motif) (Brenna and Talora 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple elements were identified, and the stress and hormone signaling-related sites are shown in Table 2 . The table describes information pertaining to functions, such as elements in response to hormones, including abscisic acid (ABRE, CE1, and MRE) (Narusaka et al 2003 ), salicylic acid (TCA element) (Liu et al 2020 ), ethylene (ERE) (Song et al 2019 ), gibberellin acid (GARE-motif, P-box and TATC-box) (Zhang et al 2017 ), auxin (TGA-element) (Xin et al 2016 ), MeJA (CGTCA-motif and TGACG-motif) (Yu et al 2018 ), temperature-responsive elements (HSE and LTR) (Wu et al . 2019 ), drought-inducible elements (MBS) (Xu et al 2019 ), wound-responsive element (WUN-motif), defense and stress element (TC-rich repeats) (Li et al 2019 ), salt-inducible element (GT1-motif), anaerobic induction element (ARE), and light- and nitrogen-inducible element (GATA-motif) (Brenna and Talora 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggests that histones are subject to numerous covalent modifications and these modifications control many aspects of chromatin function including histone mediated gene expression [ 40 , 41 ]. Increase in abundance of ribosomal proteins has been reported in maize seminal roots during drought [ 42 ] and the TCA cycle generate cellular energy metabolism and carbon skeleton supply for root development [ 43 ], likely contributed to the enhanced water uptake observed in MR.…”
Section: Resultsmentioning
confidence: 99%
“…These ribosomal proteins are associated with cell cycle regulation, replication recombination, and repair but were significantly down-regulated in LR. Taken together, the increase in abundance of histones and ribosomal proteins in MR supported the enhanced water uptake in MR possibly by modifying proteins abundance that promotes cell wall reorganization and increased root wall permeability, to allowed for more water acquisition [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we preliminarily identified the members of tomato TCA cycle [ 17 ]. The individual genes of each enzyme complex of the TCA cycle in tomato have been functionally analyzed.…”
Section: Introductionmentioning
confidence: 99%